Materialna zakonitost pri določanju davčnih obveznostih z vidika časovne veljavnosti - Podlipnik, Jernej (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2015)
In the article the author deals with the question which substantive tax rules that determine a taxpayer and tax liability (tax debt) should apply in cases where these rules change from the time a taxable event takes place and until the tax is self-assessed of levied, if the legislator has not prescribed anything in the transitional provisions in this respect. Since the Slovenian tax legislation has no general provisions for such cases, the jurisprudence has decided to either apply the provisions that were in force at the date that tax obligation occurred or provisions that were in force during the tax period to which the tax liability relates. The author is a bit critical of that position because he finds it inadequate to some extent. Therefore he suggests an amended interpretation which takes into account provisions of the Slovenian constitution and practice of the Slovenian Constitutional Court. In conclusion, the author proposes an amendment of the Slovenian tax legislation with the enactment of a general provision that would resolve such legal situations.
Keywords: davčna kultura; davčni postopek; davčno pravo; davki; pravna ureditev; tax